Bonsoir pouvez vous m'aider à factoriser les expressions suivantes: A= (-6x-3)(3x+1)-(-6x-3)(x-1) B=(4-9x)(-3x-8)+(6x-9)(-3x-8) C=4(10-6x)+4(10x+9) D=8(2-8x)+8(
Mathématiques
oceaneroche62
Question
Bonsoir pouvez vous m'aider à factoriser les expressions suivantes:
A= (-6x-3)(3x+1)-(-6x-3)(x-1)
B=(4-9x)(-3x-8)+(6x-9)(-3x-8)
C=4(10-6x)+4(10x+9)
D=8(2-8x)+8(9x-5)
E=36x²-96x+64
F=49x²+28x+4
G=81x²-126x+49
H=49x²-36
I=9x²-54x+81
J=81-9x²
Merci beaucoup bonne soirée...
A= (-6x-3)(3x+1)-(-6x-3)(x-1)
B=(4-9x)(-3x-8)+(6x-9)(-3x-8)
C=4(10-6x)+4(10x+9)
D=8(2-8x)+8(9x-5)
E=36x²-96x+64
F=49x²+28x+4
G=81x²-126x+49
H=49x²-36
I=9x²-54x+81
J=81-9x²
Merci beaucoup bonne soirée...
1 Réponse
-
1. Réponse elmessaoudiamina
bonsoir
A=(-6x-3)(3x+1)-(-6x-3)(x-1)
A=(-6x-3)[(3x+1)-(x-1)]
A=(-6x-3)(3x+1-x+1)
A=(-6x-3)(2x+2)
A=2(-6x-3)(x+1)
B=(4-9x)(-3x-8)+(6x-9)(-3x-8)
B=(-3x-8)[(4-9x)+(6x-9)]
B=(-3x-8)(4-9x+6x-9)
B=(-3x-8)(-3x-5)
C=4(10-6x)+4(10x+9)
C=4[(10-6x)+(10x+9)]
C=4(10-6x+10x+9)
C=4(4x+19)
D=8(2-8x)+8(9x-5)
D=8(2-8x+9x-5)
D=8(x-3)
E=36x^2-96x+64
E=(6x-8)(6x-8)
F=49x^2+28x+4
F=(7x+2)(7x+2)
G=81x^2-126x+49
G=(9x-7)(9x-7)
H=49x^2-36
H=(7x-6)(7x+6). identité remarquable
I=9x^2-54x+81
I=9(x^2-6x+9)
I=9(x-3)(x-3)
J=81-9x^2
J=9(9-x^2). identité remarquable
J=9(3-x)(3+x)